Analisis Kritis Terhadap Daya Batas Asas Kebebasan Berkontrak Dalam Kitab Undang-Undang Hukum Perdata - Herman Herman; Heri Tahir; Ririn Nurfaathirany Heri; Firmansyah Firmansyah (Postgraduate Program in Law, Universitas Pattimura, 2022)
Introduction: The limiting power of the principle of freedom of contract in the Civil Code and its development.Purposes of the Research: In particular, it will examine and analyze the principle of freedom of contract in terms of the implementation of this principle and also describe the articles contained in the Criminal Code related to the interpretation of the principle of freedom of contract.Methods of the Research: The research was conducted using a normative juridical method with a c statutory approach, conceptual approach and comparative approach a by specifically analyzing the performance of the institution and its authority in the implementation of law enforcement in the Maluku Sea based on the legislation which was then analyzed qualitatively.Results of the Research: The results of the research on a critical analysis of the power of limiting the principle of freedom of contract in the Civil Code can be concluded that the limitation of the principle of freedom of contract has actually been stated in several articles in the Civil Code, by linking the articles in the Civil Code regarding the provisions in making an agreement, freedom of contract is not only guaranteed in the law on treaties, but at the same time that freedom must be framed by other articles. Along with the restrictions on freedom of contract contained in and outside the Civil Code, the tendency to limit freedom of contract, especially its manifestation in giving a more important role to the value of decency and feasibility (redelijkheid en bijlijkheid), good faith, and public order, therefore when contracts are made, these values must be accommodated.